2015
DOI: 10.3923/ijzr.2015.151.159
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Parasites and Ecto-Symbiont in Wild Mud Crab, Genus Scylla from Terengganu Coastal Water, Malaysia: Prevalence and Mean Intensity

Abstract: Seventy three sample of wild mud crab genus Scylla were collected from setiu wetland, Terengganu coastal waters, Malaysia with the measured of Carapace Width (CW) and Body Weight (BW) 8.9±0.1 and 103.9±3.8, respectively. The percentage prevalence of parasites from these studies is 81.9% and the mean intensity was 13. The total number of 887 parasites that were collected includes barnacle (Octolasmis spp.), ciliates, sessile protozoan (Epistylis sp.), nematode and copepod. The higher number of parasites that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The parasite prevalence was calculated from the total number of infected samples divided by the number of samples examined. The prevalence of parasites was calculated using an equation that refers to [1]:…”
Section: • Prevalence Of Ectoparasitementioning
confidence: 99%
See 1 more Smart Citation
“…The parasite prevalence was calculated from the total number of infected samples divided by the number of samples examined. The prevalence of parasites was calculated using an equation that refers to [1]:…”
Section: • Prevalence Of Ectoparasitementioning
confidence: 99%
“…Scylla paramamosain is very often found in continental regions of the South China Sea to the South Java Sea. The four mangrove crab species are associated with another species in the same geographic area [1] To fulfill the supply of mangrove crab commodities in Indonesia generally rely on catches in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, parasites infecting mud crabs, especially S. olivacea, in Malaysian waters include ciliates, nematodes, copepods and barnacles (Octolasmis spp.). Being the most abundant among other parasites (71.1% prevalence) (Ihwan et al, 2015), Octolasmis barnacles are often found in the respiratory chambers of mud crabs (Jeffries et al, 1989) and pose minimal threat to their hosts as they do not feed on host tissues (Gannon and Wheatly, 1992). Recently, however, the occurrence of rhizocephalan barnacles Sacculina beauforti (Sacculinidae) on mud crab Scylla olivacea was reported, with a high prevalence rate of 42.27% (Waiho et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%